Self-Healing Concept in The Quran: An Analysis of Sakana and Ithma'anna Words - A. Syahid Robbani*; Abdul Mukhlis; Rika Astari; Nur Aini Maryamah; Alifatul Aufa (Riwayat: Educational Journal of History and Humanities, 2023)
Self-healing term is widely used by the youth generation lately in the cyber and real world. People comprehend the term as the effort to heal oneself from heart discomfort caused by a failure, pressure, anxiety, disappointment, insecurity, et cetera, and the effort to seek inner serenity and tranquility. However, unfortunately, some people choose to do self-healing in the wrong and deviant way. Therefore, this research aims to straighten up and reveal the self-healing concept in the Quran by analyzing the words Sakana and Ithma'anna and their derivation embodying the meaning of tranquility. This study is library research by implementing a semantic approach. The applied data collection method was documentation using primary and secondary data, i.e., the Quran, Al-Misbah, Al-Qurthubi, and Ibn Kathir exegesis. This research result indicates that Allah sends down tranquility for those with mental readiness and decorates themselves with commendable qualities. This research also conveys several deeds that can be done as self-healing, which in reality is contrary to the habits of today's younger generation. Eventually, the serenity that all man desires is eternal tranquility, which is included in the group of people who are called upon by Allah and addressed by 'O tranquil soul' when he dies and on the Day of Resurrection.